2021
DOI: 10.3390/en14144363
|View full text |Cite
|
Sign up to set email alerts
|

Trade, Climate and Energy: A New Study on Climate Action through Free Trade Agreements

Abstract: Efforts to tackle climate change are taking place on multiple fronts. This includes trade, an increasingly important defining feature of the global economy. In recent years, free trade agreements (FTAs) have become the primary mechanism of trade policy and diplomacy. This study examines the development of climate action measures in FTAs and discusses what difference they can make to tackling climate change. Its primary source research is based on an in-depth examination of FTAs in force up to 2020. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…A study of various climate action provisions within existing RTAs revealed that 60% of the provisions fell within the domain of clean-energy-sector development. 51 Energy is the fundamental element in the trade-climate relationship. In this study, six interrelated empirical domains in the trade-climate area were discussed, concluding that energy is an element in all six of them.…”
Section: International Trade Law [2024]mentioning
confidence: 99%
“…A study of various climate action provisions within existing RTAs revealed that 60% of the provisions fell within the domain of clean-energy-sector development. 51 Energy is the fundamental element in the trade-climate relationship. In this study, six interrelated empirical domains in the trade-climate area were discussed, concluding that energy is an element in all six of them.…”
Section: International Trade Law [2024]mentioning
confidence: 99%
“…Each node represents a PTA member, and each tie indicates that they are connected by an agreement with at least one climate provision. As the figure illustrates, the EU is the most central actor in the network (for further information about the EU as climate norms leader in PTAs, see also Dent, 2021 andBenson et al, 2022).…”
Section: Policy Diffusion and Environmental Provisionsmentioning
confidence: 99%
“…Another common view was that trade-induced improvements in resource efficiency through comparative advantage-based specialisation would help reduce emissions. Counterviews to this, such as the 'Jevons Paradox' argument that efficiency-driven lowering of prices can lead to higher levels of resource-processing and mass-production, are not considered [144]. More broadly, all GEIs underlined the importance of an open and stable global trading system for climate protection.…”
Section: Ideological Principles Concepts and Theoriesmentioning
confidence: 99%
“…While FTA/RTAs promote trade liberalisation and mutual market access between signatory trade partners, they are increasingly viewed as trade regulatory treaties entailing inter-governmental co-operation on market rule-setting and market creation. Their climate-relevant provisions furthermore have a strong focus on inter-governmental and multilateral co-operation rather than liberalisation per se [68,144]. Other prominent MBI-related terms included carbon taxes (0.22), emissions trading (0.19), carbon border adjustments (0.16) and carbon pricing (0.16).…”
Section: Market-based Instruments (Mbis)mentioning
confidence: 99%